SIKAP DAN PERMINTAAN KONSUMEN DALAM MENGONSUMSI KOPI (KASUS PADA NELAYAN DI KECAMATAN TELUK BETUNG TIMUR KOTA BANDAR LAMPUNG) - Renni Dwi Rahmawati; Teguh Endaryanto; Eka Kasymir (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
Coffee contains caffeine, which is often consumed by fishermen as their choice when working at night. This research aims to study fishermen's attitude toward consuming coffee and the factors that influence fishermen's demand for coffee in Teluk Betung Timur Sub-district.  This research used a survey method with direct interviews using a questionnaire.  Research was conducted in Teluk Betung Timur Sub-district in June-July 2020, using purposive sampling. Respondents were 54 fishermen with the criteria of fishermen who consume coffee at least four times in a month.  Research data were analyzed descriptive quantitatively using a model of multiattribute Fishbein and multiple linear regression.  Based on research results, Fishermen in Teluk Betung Timur Sub District Bandar Lampung City have a pretty good attitude category on consuming coffee with the most preferred attribute after-drink effect. The factors that influence fishermen's demand for coffee are the price of energy drinks, sugar prices, and types of coffee.Key words: Attitude in consuming, coffee, demand.